Post-stroke depression in rehabilitation - Yookarajah, Uma Devi; Abdul Latif, Lydia (University of Malaya Medical Centre, 2020)
Depression is a frequent companion of stroke. It is associated with a degree of functional impairment that might adversely affect rehabilitation. A study was carried out to determine the rate of self-reported depression at admission and after six months, and the associated factors, in patients with stroke who were referred for rehabilitation. A multiple binary logistic regression was used to determine the associated factors at six months. Depression was recorded in 45% of patients at admission and in 39% at six months after the stroke. Patients who were employed, those who were depressed at admission, those who did not return to work and those who did not return to driving six months after stroke, were significantly associated with depression. © 2020, Faculty of Medicine, University of Malaya. All rights reserved.